What does embarrassment have to do with our choice of brands? - Singapore Management University (Institutional Knowledge at Singapore Management University, 2018)
Everyone experiences moments of embarrassment – when their credit cards are rejected at the checkout, they are wearing their T-shirt inside out, or have to buy tampons or condoms in a store. When people are embarrassed it is only natural they behave differently to try to make themselves feel better. But how do they cope with feeling embarrassed? What types of strategies do they adopt and how does all this relate to their self-esteem?